Foreign Exchange Rate: How To Predict And How Accurate Are The Predictions - Li, Shuhao (2015)
This paper is for the MSc finance and investment dissertation. The main goal of this paper is to show how to predict the foreign exchange rate and to discuss whether the methods used for the prediction are efficient. Moreover, this paper will mainly focus on the exchange rates in the developing countries.